KAJIAN KETIMPANGAN PENDAPATAN EKONOMI KABUPATEN BONE - Misbahuddin Misbahuddin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
The study of income inequality in the economy into a discussion of this study is that the level of inequality of income distribution in Bone regency shown as relatively high value of the gini ratio. There are differences in the level of inequality between districts. Takkalala the District is a district with the lowest levels of inequality Ulaweng while the District is a district with the highest level of inequality. Based on the results of statistical analysis, the level of public revenues, the most influential factor in the level of economic ketipangan district Bone is the level of education, the head of the family, number of dependents, and investment value.